2016
DOI: 10.1120/jacmp.v17i5.6327
|View full text |Cite
|
Sign up to set email alerts
|

Spot scanning proton therapy minimizes neutron dose in the setting of radiation therapy administered during pregnancy

Abstract: This is a real case study to minimize the neutron dose equivalent (H) to a fetus using spot scanning proton beams with favorable beam energies and angles. Minimum neutron dose exposure to the fetus was achieved with iterative planning under the guidance of neutron H measurement. Two highly conformal treatment plans, each with three spot scanning beams, were planned to treat a 25‐year‐old pregnant female with aggressive recurrent chordoma of the base of skull who elected not to proceed with termination. Each pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…The observed secondary cancer incidence at 10 years was significantly decreased from 8.6% with photons to 5.4% with protons (Hazard ratio of 0.54; p <0.09). Importantly protons were delivered to patients with a passive scattering delivery paradigm that produced more neutrons than PBS (46,47). The latter delivery may thus produce even less radiation-induced malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The observed secondary cancer incidence at 10 years was significantly decreased from 8.6% with photons to 5.4% with protons (Hazard ratio of 0.54; p <0.09). Importantly protons were delivered to patients with a passive scattering delivery paradigm that produced more neutrons than PBS (46,47). The latter delivery may thus produce even less radiation-induced malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…171 The subject of the out-offield dose is also related to the treatment of pregnant patients and patients with implanted cardiac pacemakers and defibrillators. Published data on the comparative out-of-field dose from proton therapy are helpful for the assessment, 168,[172][173][174][175] and the management of proton therapy patients with implanted cardiac pacemakers and defibrillators is specifically addressed in TG-203. 176…”
Section: Out-of-field Dose From Proton Therapymentioning
confidence: 99%
“…Although passive irradiation was mainstream in those days, scanning irradiation has become the method of today. Several studies reported that the neutron dose by scanning method is much lower by an order of one or two than that by passive method . Thus, taking 1/10 as a typical value of neutron dose by scanning irradiation compared to that by passive irradiation, the number of malfunctions by particle beams is reduced as additionally drawn in Fig.…”
Section: Discussionmentioning
confidence: 84%